2021
DOI: 10.1111/vco.12760
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of dogs diagnosed with canine inflammatory mammary cancer treated with metronomic cyclophosphamide, a cyclooxygenase‐2 inhibitor and toceranib phosphate

Abstract: Canine inflammatory mammary cancer (IMC) is highly malignant, invasive and a therapeutic challenge, because effective medical treatment is still unavailable. This retrospective study compares the efficacy of an oral cyclooxygenase‐2 (COX‐2) inhibitor combined with toceranib phosphate and oral cyclophosphamide (multi‐drug therapy [MT]) with COX‐2 inhibitor therapy alone (single‐drug therapy [ST]) in dogs diagnosed with secondary IMC. Clinical response, adverse events, overall survival time (OST), disease‐free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Metronomic chemotherapy is emerging as a promising alternative that results in fewer adverse reactions and lower stress levels [ 6 ]. However, in veterinary medicine, there are still few studies related to its effectiveness, whether it is isolated or associated with conventional chemotherapy, especially in the case of mammary tumors in female dogs [ 7 , 8 , 9 , 10 ]. Nevertheless, the clinical implementation of new treatment combinations with low-dose chemotherapy requires studies to select effective treatment combinations for each tumor type and population [ 8 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metronomic chemotherapy is emerging as a promising alternative that results in fewer adverse reactions and lower stress levels [ 6 ]. However, in veterinary medicine, there are still few studies related to its effectiveness, whether it is isolated or associated with conventional chemotherapy, especially in the case of mammary tumors in female dogs [ 7 , 8 , 9 , 10 ]. Nevertheless, the clinical implementation of new treatment combinations with low-dose chemotherapy requires studies to select effective treatment combinations for each tumor type and population [ 8 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that metronomic chemotherapy (5‐fluorouracil + VNR) cotargeting TNBC cells and endothelial cells effectively inhibits cell regrowth and migration via FAK/VEGFR2/VEGF downregulation and autophagy/apoptosis activation 30 . Owing to the diverse antitumor mechanisms of metronomic chemotherapy, a growing number of studies are currently endeavoring to integrate metronomic chemotherapy with other interventions, including targeted therapy and immunotherapy, among others, for the purpose of treating tumors 31–35 . In recent years, metronomic chemotherapy has gained widespread application in a range of cancers, including BC, 36,37 esophageal and gastroesophageal cancer, 38 lung cancer, 39 pancreatic cancer, 40 ovarian cancer, 41 and others.…”
Section: Discussionmentioning
confidence: 99%
“…In women with BC, multimodal (adjuvant or neoadjuvant) chemotherapy uses anthracyclins (doxorubicin, epirubicin), taxanes (paclitaxel, docetaxel) and cyclophosphamide (Pernaut et al, 2018). In small animals with MCs, apart from canine inflammatory MCs, chemotherapy is rarely multimodal, which may contribute to the limited results obtained so far in terms of survival improvement (Alonso‐Miguel et al, 2022; Petrucci et al, 2021; Valdivia et al, 2021). A progress in canine/feline MC therapy can be expected by further developments in multimodal chemotherapy.…”
Section: Systemic Cancer Controlmentioning
confidence: 99%